Groundwater-connected art: Practicing arts-based research to enrich how hydrogeology engages people, place, and other disciplines - Tom Gleeson (Hydrogeology Journal, 2026)
Groundwater depletion, contamination and governance challenges persist despite decades of research. Scientific methods are crucial yet seem insufficient to inspire the emotional, cultural and community connections needed for real change—groundwater challenges and opportunities may not be reaching enough hearts and minds. This perspective article invites a bold shift: integrating arts-based research into hydrogeology. Hydrogeologists, in collaboration with social scientists, artists, and communities, might spark more powerful connections to groundwater by blending art forms such as drama, visual art, storytelling, and music with scientific practice. This article unfolds through a series of invitations spanning art, community engagement and learning from related disciplines that have embraced arts-based research. I introduce the concept of groundwater-connected art as both process and expression, expanding how groundwater could be represented and understood. Examples across artistic practices exist and could be expanded through expressions of groundwater tastes, smells, sounds, landscapes, cultures, and connections in community and into the future. Arts-based research offers methods to bridge gaps across disciplines, strengthen participatory and community-engaged approaches, elevate cultural and relational dimensions of groundwater, and align with emerging priorities in socio-hydrogeology. Integrating art is not without challenges, including questions of role, rigor, ethics and positionality, but creative processes could make hydrogeology more human, equitable and impactful. This article invites hydrogeologists to embrace creativity and collaboration with artists, social scientists, and communities—which could change how we engage with, value and care for this often invisible resource.

Current trends and biases in groundwater modelling using the community-driven groundwater model portal (GroMoPo) - Daniel Zamrsky; Sacha Ruzzante; Kyle Compare; Daniel Kretschmer; Sam Zipper; Kevin M. Befus; Robert Reinecke; Yara Pasner; Tom Gleeson; Kristen Jordan; Mark Cuthbert; Anthony M. Castronova; et al. (Hydrogeology Journal, 2025)
Groundwater, Earth’s largest nonfrozen freshwater reservoir, is vital for water supply security. Groundwater models help to manage complex domestic, agricultural, and industrial water demands while preserving ecosystem health under climate change. The community-driven groundwater model portal (GroMoPo) hosts groundwater model metadata to analyse biases and distribution of groundwater models. Over 450 models are currently featured on GroMoPo, with most models from high-GDP countries at local-to-regional scales. The GroMoPo initiative addresses current knowledge gaps and facilitates future collaboration and data sharing.

Assessment of spatiotemporal risks for nationwide groundwater nitrate contamination - Yang Zhan; Zhilin Guo; Sacha Ruzzante; Tom Gleeson; Charles B. Andrews; Vladan Babovic; Chunmiao Zheng (Science of The Total Environment, 2024)

Reply to Comment on “Applying a science-forward approach to groundwater regulatory design”: Paper published in Hydrogeology Journal (2023) 31:853–871, by Deborah Curran, Tom Gleeson and Xander Huggins - Deborah Curran; Tom Gleeson; Xander Huggins (Hydrogeology Journal, 2024)

Applying a science-forward approach to groundwater regulatory design - Deborah Curran; Tom Gleeson; Xander Huggins (Hydrogeology Journal, 2023)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Crustal permeability - Steve Ingebritsen; Tom Gleeson (Hydrogeology Journal, 2017)

The limits of increasing food production with irrigation in India - Mikhail Smilovic; Tom Gleeson; Stefan Siebert (Food Security, 2015)

Editors’ Message: The 2013 Editors’ Choice articles, a new editor, and the 2013 ‘Coolest Paper’ award - Clifford Voss; Matthew Currell; Tom Gleeson (Hydrogeology Journal, 2014)

Perceptions of scale in hydrology: what do you mean by regional scale? - Tom Gleeson; Dawn Paszkowski (Hydrological Sciences Journal, 2014)

The return of groundwater quantity: a mega-scale and interdisciplinary “future of hydrogeology”? - Tom Gleeson; Michael Cardiff (Hydrogeology Journal, 2013)

Reinvasion by ship rats (Rattus rattus) of forest fragments after eradication - Carolyn M. King; John G. Innes; Dianne Gleeson; Neil Fitzgerald; Tom Winstanley; Barry O’Brien; Lucy Bridgman; Neil Cox (Biological Invasions, 2011)